COMPOSITION AND THERMAL PROPERTIES OF QUATERNARY MIXTURES OF PALM OIL:PALM STEARIN:SOYBEAN OIL:COCOA BUTTER - MARIKKAR, J.M.N.; YANTY, N.A.M.; PACIULLI, M.; MISKANDAR, M.S.; CHIAVARO, E. (Italian Journal of Food Science, 2018)
Pam oil (PO) is a semi-solid substance with potential functional lipid characteristics. A study was carried out to evaluate the effect of addition of soybean oil (SBO), palm stearin (PS) and cocoa butter (CB) on the solidification behavior of PO to formulate a mixture to become similar to lard (LD). A total of three mixtures were prepared: PO:PS:SBO:CB (38:5:52:5), PO:PS:SBO:CB (36:5:54:5) PO:PS:SBO:CB (34:5:56:5) (w/w), and identified by the mass ratio of PO to PS, CB and SBO. The fat mixtures were compared with lard in terms of the fatty acid and triacylglycerol compositions using gas chromatography and high performance liquid chromatography, thermal properties using differential scanning calorimetry (DSC) and solid fat content (SFC) using p-nuclear magnetic resonance (p-NMR). Although there were considerable differences between lard and the fat mixtures with regard to fatty acid and triacylglycerol compositions, some similarities were seen on their DSC thermal properties and solid fat content profile. Of the fat mixtures, PO:PS:SBO:CB (38:5:52:5) displayed closer similarity to lard by having least difference to SFC profile throughout the temperature range and a common DSC thermal transition at around -3.59 °C.